1992
DOI: 10.1007/bf00636216
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill validation of an over-ground walking test to predict peak oxygen consumption

Abstract: The purpose of this study was to determine whether a test developed to predict maximal oxygen consumption (VO2max) during over-ground walking, was similarly valid as a predictor of peak oxygen consumption (VO2) when administered during a 1-mile (1.61 km) treadmill walk. Treadmill walk time, mean heart rate over the last 2 full min of the walk test, age, and body mass were entered into both generalized (GEN Eq.) and gender-specific (GSP Eq.) prediction equations. Overall results indicated a highly significant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 13 publications
1
24
1
Order By: Relevance
“…Peak VO 2 (mL/kg/min) was estimated as a function of time taken to complete the one-mile walk, heart rate during the walk, age, body mass index, and gender. In previous research, estimated peak VO 2 using this fitness test has shown correlations with observed peak VO2 of r ≥ .85 among community dwelling adults [21, 22]. …”
Section: Methodsmentioning
confidence: 98%
“…Peak VO 2 (mL/kg/min) was estimated as a function of time taken to complete the one-mile walk, heart rate during the walk, age, body mass index, and gender. In previous research, estimated peak VO 2 using this fitness test has shown correlations with observed peak VO2 of r ≥ .85 among community dwelling adults [21, 22]. …”
Section: Methodsmentioning
confidence: 98%
“…After completing the EMA instruction session, participants are scheduled for their final baseline assessment session—a one-mile walk test to provide an indication of baseline fitness (Widrick, Ward, Ebbeling, Clemente, & Rippe, 1992). …”
Section: Baseline Proceduresmentioning
confidence: 99%
“…Make physical activity assessment a "vital sign" As Pate et al recommend, asking and assessing physical activity as a vital sign demonstrates that the clinician believes that physical activity is as important as other vital signs and that the patient should as well. 4. Employ algorithms that match the current level of physical activity to specific programs designed to enhance physical activity Many important clinical decisions are now based on evidence-based algorithms that are employed at hospitals across the United States.…”
Section: Learn Motivational Interviewingmentioning
confidence: 99%